Producciòn De Leche Y Carne De Bùfala (Bubalus Bubalis) - Ardila Beltrán, María Paula; Gutiérrez Pérez, Juan Daniel (Universidad Antonio Nariño, 2025)
The water buffalo (Bubalus bubalis) is an animal that was introduced to Colombia in the 1960s, its arrival came from the islands of Trinidad and Tobago, located in the Caribbean, since then an industry began to form around these animals, with the aim of making the most of these animals for human benefit, several breeds of these animals arrived in Colombia, however the ones that showed the most dominance in the territory were the Murrah breed, they are animals with very good milk production and good quality meat, which makes it an excellent alternative as a source of energy of animal origin, showing favorable results in the percentages of protein, minerals, cholesterol and calories, compared to beef. Its population has been increasing since 2021 according to data reported by the ICA (Colombian Institute of Agriculture) and the reported farms are distributed over a large part of the national territory, with Cundinamarca being the department with the most farms and the Caribbean with the most buffalo presence.